2010
DOI: 10.1590/s1807-55092010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Semelhança fraterna nos níveis de aptidão física: um estudo na população rural de Calanga, Moçambique

Abstract: Este estudo teve dois propósitos: 1) determinar agregação familiar em diferentes indicadores da aptidão física, e 2) a sua componente genética (h²). A amostra foi constituída por 330 sujeitos (174 meninos e 156 meninas) dos sete aos 17 anos de idade, pertencentes a 132 famílias de Calanga, uma localidade rural de Moçambique. A aptidão física foi avaliada com os seguintes testes: sentar e alcançar, impulsão horizontal, tempo de suspensão na barra, dinamometria manual, corrida da milha, abdominais e corrida vaiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…The pattern of intraclass correlations found in our study suggests that SS pairs have greater resemblance in GMC than BS and BB pairs. This result differs from other reports with non-twin siblings for some physical fitness tests, in which BB pairs showed higher similarity (Saranga et al 2010;Pereira et al 2017), but is similar to the pattern observed in physical activity resemblance (Pereira et al 2018). One possible explanation for the observed differences is related to the dynamics of the traditional structure of Peruvian families.…”
Section: Discussioncontrasting
confidence: 99%
“…The pattern of intraclass correlations found in our study suggests that SS pairs have greater resemblance in GMC than BS and BB pairs. This result differs from other reports with non-twin siblings for some physical fitness tests, in which BB pairs showed higher similarity (Saranga et al 2010;Pereira et al 2017), but is similar to the pattern observed in physical activity resemblance (Pereira et al 2018). One possible explanation for the observed differences is related to the dynamics of the traditional structure of Peruvian families.…”
Section: Discussioncontrasting
confidence: 99%
“…Since we controlled for between‐year differences in BMI, the aforementioned decline in flexibility cannot be explained by a relationship between increased BMI and a negative trend in flexibility, as has been explained elsewhere 18 . Saranga and colleagues 46 have attributed the deterioration in flexibility to a decline in physical activity and unstructured play 46 . Indeed, there is a consensus that flexibility gradually declines in children and adolescents, 7 mostly measured with a similar methodological testing procedure and using the sit‐and‐reach test as an indicator of flexibility.…”
Section: Discussionmentioning
confidence: 96%